Screening for PAH - How to Reduce Delay in CTD-PAH Diagnosis - Yeon-Ah Lee (Journal of Clinical Rheumatology and Immunology)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a diverse clinical presentation, including pulmonary involvement. While pulmonary complications are common in SLE, a subset of patients develop pulmonary arterial hypertension (PAH), a life-threatening condition characterized by elevated pulmonary vascular resistance and right ventricular dysfunction. Early detection and timely management are crucial for improving outcomes in this vulnerable patient population. This lecture will focus on the importance of PAH screening in SLE, highlighting the clinical insights and management strategies for this challenging condition. The lecture will begin by reviewing the epidemiology and pathophysiology of PAH in SLE, emphasizing the role of autoimmunity, inflammation, and microvascular dysfunction. The clinical manifestations of PAH in SLE, including dyspnea, fatigue, chest pain, and syncope will be discussed. These symptoms may be subtle and often overlap with other SLE manifestations, making early recognition challenging. The lecture will then delve into the importance of PAH screening in SLE. We will discuss the current recommendations for screening, including the use of blood markers to evaluate the PAH risk factors, echocardiography to assess right ventricular function and pulmonary artery pressure. We will also explore the role of other diagnostic tools, such as NT-proBNP test, pulmonary function tests and right heart catheterization, in confirming the diagnosis of PAH. The management strategies for PAH in SLE will then be focused, emphasizing the importance of multidisciplinary care involving rheumatologists, pulmonologists, cardiologists, and other specialists. We will explore the current evidence-based guidelines for pharmacotherapy, including the role of vasodilators, endothelin receptor antagonists, and phosphodiesterase type 5 inhibitors. Finally, the lecture will end with real-world cases, highlighting the heterogeneity of the disease, the need of identifying the disease early, and the need for personalized medicine approaches to improve outcomes for this vulnerable patient population. This lecture aims to equip clinicians with the knowledge and tools to effectively identify PAH in SLE, facilitating early diagnosis and timely initiation of appropriate management strategies, ultimately improving patient outcomes.